Variability of Vertical Total Electron Content Gradients in the Brazilian Sector - Espejo, Teddy Modesto Surco; Costa, Emanoel; de Paula, Eurico Rodrigues; Moraes, Alison de Oliveira; Monico, Joao Francisco Galera (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Ground Based Augmentation Systems are designed to meet demanding requirements during airport approach and landing sections of aircraft routes. It computes corrected and smoothed differential corrections and other information. These messages are transmitted to aircraft, which may use the corrections to improve their position estimation. However, residual correction errors remain, due to ionospheric spatial and temporal gradients between Ground Based Augmentation System reference receivers and approaching aircrafts. Large vertical ionospheric delay gradients detected during combinations of extreme geophysical environments indicate that there are problematic conditions for Ground Based Augmentation System operation over the Brazilian region. Motivated by the above conditions, data from Rede Brasileira de Monitoramento Contínuo, the Brazilian public network of dual-frequency Global Navigation Satellite System receivers operated by Instituto Brasileiro de Geografia e Estatística were analyzed to estimate ionospheric vertical Total Electron Content gradients. The effects from different locations (represented by the dip latitude) and geophysical conditions (represented by solar activity, season, and local time) on variations of ionospheric vertical Total Electron Content gradients have been statistically quantified. The results from the present work provide information to more detailed performance assessments of Ground Based Augmentation System procedures under equatorial and low-latitude ionospheric regions, aimed at flexibly delimiting the conditions for feasible operation in such regions.
Keywords: Aircraft; Airports; Delays; equatorial and low-latitude ionosphere; Global Positioning System; Ground Based Augmentation Systems; ionospheric decorrelation; ionospheric vertical Total Electron Content gradients; Monitoring; Receivers; Rede Brasileira de Monitoramento Contínuo; Standards